Difference between revisions of "2022 AIME I Problems/Problem 15"
m (→Solution 1 (geometric interpretation)) |
m (→Solution 1 (geometric interpretation)) |
||
Line 10: | Line 10: | ||
==Solution 1 (geometric interpretation)== | ==Solution 1 (geometric interpretation)== | ||
− | First, | + | First, let define a triangle with side lengths <math>\sqrt{2x}</math> <math>\sqrt{2z}, and </math>S<math>, with </math>S<math>'s altitude </math>\sqrt{xz}<math>. </math>S = \sqrt(2x - xz) + \sqrt(2z - xz)<math>, the left side of one equation in the problem. |
− | We can symmetrically apply this to the two other triangles | + | Let </math>\theta<math> be angle opposite the side with length </math>\sqrt{2x}<math>. Then the altitude has length </math>\sqrt{2z} \cdot \sin(\theta) = \sqrt{xz}<math> and thus </math>\sin(\theta) = \sqrt{\frac{x}{2}}<math>, so </math>x=2\sin^2(\theta)<math> and the side length </math>\sqrt{2x}<math> is equal to </math>2\sin(\theta)<math>. |
+ | |||
+ | We can symmetrically apply this to the two other equations/triangles. | ||
+ | |||
+ | By law of sines, we have </math>\frac{2\sin(\theta)}{\sin(\theta)} = 2R \to R=1<math> is the circumradius of that triangle. Hence. we calculate that with </math>l=1, \sqrt{2}<math>, and </math>\sqrt{3}<math>, the angles from the third side with respect to the circumcenter are </math>120^{\circ}, 90^{\circ}<math>, and </math>60^{\circ}<math>. This means that by half angle arcs, we see that we have in some order, </math>x=2\sin^2(\alpha)<math>, </math>x=2\sin^2(\beta)<math>, and </math>z=2\sin^2(\gamma)<math> (not necessarily this order, but here it does not matter due to symmetry), satisfying that </math>\alpha+\beta=180^{\circ}-\frac{120^{\circ}}{2}<math>, </math>\beta+\gamma=180^{\circ}-\frac{90^{\circ}}{2}<math>, and </math>\gamma+\alpha=180^{\circ}-\frac{60^{\circ}}{2}<math>. Solving, we get </math>\alpha=\frac{135^{\circ}}{2}<math>, </math>\beta=\frac{105^{\circ}}{2}<math>, and </math>\gamma=\frac{165^{\circ}}{2}$. | ||
We notice that <cmath>[(1-x)(1-y)(1-z)]^2=[\sin(2\alpha)\sin(2\beta)\sin(2\gamma)]^2=[\sin(135^{\circ})\sin(105^{\circ})\sin(165^{\circ})]^2</cmath> <cmath>=\left(\frac{\sqrt{2}}{2} \cdot \frac{\sqrt{6}-\sqrt{2}}{4} \cdot \frac{\sqrt{6}+\sqrt{2}}{4}\right)^2 = \left(\frac{\sqrt{2}}{8}\right)^2=\frac{1}{32} \to \boxed{033}. \blacksquare</cmath> | We notice that <cmath>[(1-x)(1-y)(1-z)]^2=[\sin(2\alpha)\sin(2\beta)\sin(2\gamma)]^2=[\sin(135^{\circ})\sin(105^{\circ})\sin(165^{\circ})]^2</cmath> <cmath>=\left(\frac{\sqrt{2}}{2} \cdot \frac{\sqrt{6}-\sqrt{2}}{4} \cdot \frac{\sqrt{6}+\sqrt{2}}{4}\right)^2 = \left(\frac{\sqrt{2}}{8}\right)^2=\frac{1}{32} \to \boxed{033}. \blacksquare</cmath> |
Revision as of 11:28, 25 March 2023
Contents
Problem
Let
and
be positive real numbers satisfying the system of equations:
Then
can be written as
where
and
are relatively prime positive integers. Find
Solution 1 (geometric interpretation)
First, let define a triangle with side lengths
S
S
\sqrt{xz}
S = \sqrt(2x - xz) + \sqrt(2z - xz)$, the left side of one equation in the problem.
Let$ (Error compiling LaTeX. Unknown error_msg)\theta\sqrt{2x}
\sqrt{2z} \cdot \sin(\theta) = \sqrt{xz}
\sin(\theta) = \sqrt{\frac{x}{2}}
x=2\sin^2(\theta)
\sqrt{2x}
2\sin(\theta)$.
We can symmetrically apply this to the two other equations/triangles.
By law of sines, we have$ (Error compiling LaTeX. Unknown error_msg)\frac{2\sin(\theta)}{\sin(\theta)} = 2R \to R=1l=1, \sqrt{2}
\sqrt{3}
120^{\circ}, 90^{\circ}
60^{\circ}
x=2\sin^2(\alpha)
x=2\sin^2(\beta)
z=2\sin^2(\gamma)
\alpha+\beta=180^{\circ}-\frac{120^{\circ}}{2}
\beta+\gamma=180^{\circ}-\frac{90^{\circ}}{2}
\gamma+\alpha=180^{\circ}-\frac{60^{\circ}}{2}
\alpha=\frac{135^{\circ}}{2}
\beta=\frac{105^{\circ}}{2}
\gamma=\frac{165^{\circ}}{2}$.
We notice that
- kevinmathz
Solution 2 (pure algebraic trig, easy to follow)
(This eventually whittles down to the same concept as Solution 1)
Note that in each equation in this system, it is possible to factor ,
, or
from each term (on the left sides), since each of
,
, and
are positive real numbers. After factoring out accordingly from each terms one of
,
, or
, the system should look like this:
This should give off tons of trigonometry vibes. To make the connection clear,
,
, and
is a helpful substitution:
From each equation
can be factored out, and when every equation is divided by 2, we get:
which simplifies to (using the Pythagorean identity
):
which further simplifies to (using sine addition formula
):
Without loss of generality, taking the inverse sine of each equation yields a simple system:
giving solutions
,
,
. Since these unknowns are directly related to our original unknowns, there are consequent solutions for those:
,
, and
. When plugging into the expression
, noting that
helps to simplify this expression into:
Now, all the cosines in here are fairly standard:
,
,
and
. With some final calculations:
This is our answer in simplest form
, so
~Oxymoronic15
solution 3
Let , rewrite those equations
;
and solve for
Square both sides and simplify, to get three equations:
Square both sides again, and simplify to get three equations:
Subtract first and third equation, getting ,
Put it in first equation, getting ,
Since ,
and so the final answer is
~bluesoul
Solution 4
Denote ,
,
.
Hence, the system of equations given in the problem can be written as
Each equation above takes the following form:
Now, we simplify this equation by removing radicals.
Denote and
.
Hence, the equation above implies
Hence, .
Hence,
.
Because and
, we get
.
Plugging this into the equation
and simplifying it, we get
Therefore, the system of equations above can be simplified as
Denote .
The system of equations above can be equivalently written as
Taking , we get
Thus, we have either or
.
:
.
Equation (2') implies .
Plugging and
into Equation (2), we get contradiction. Therefore, this case is infeasible.
:
.
Plugging this condition into (1') to substitute , we get
Taking , we get
Taking (4) + (5), we get
Hence, .
Therefore,
Therefore, the answer is .
\end{solution}
~Steven Chen (www.professorchenedu.com)
Solution 5
Let ,
, and
. Then,
Notice that ,
, and
. Let
,
, and
where
,
, and
are real. Substituting into
,
, and
yields
Thus,
so
. Hence,
so
, for a final answer of
.
Remark
The motivation for the trig substitution is that if , then
, and when making the substitution in each equation of the initial set of equations, we obtain a new equation in the form of the sine addition formula.
~ Leo.Euler
Solution 6 (Geometric)
In given equations, so we define some points:
Notice, that
and each points lies in the first quadrant.
We use given equations and get some scalar products:
So
Points and
are simmetric with respect to
Case 1
Case 2
vladimir.shelomovskii@gmail.com, vvsss
Video Solution
~Math Gold Medalist
Video Solution
https://www.youtube.com/watch?v=ihKUZ5itcdA
~Steven Chen (www.professorchenedu.com)
See Also
2022 AIME I (Problems • Answer Key • Resources) | ||
Preceded by Problem 14 |
Followed by Last Problem | |
1 • 2 • 3 • 4 • 5 • 6 • 7 • 8 • 9 • 10 • 11 • 12 • 13 • 14 • 15 | ||
All AIME Problems and Solutions |
The problems on this page are copyrighted by the Mathematical Association of America's American Mathematics Competitions.